The Materialism Of Mary In Angel Gracia’s Film “From Prada To Nada” Sociological Approach - Sundari Saputri; Dodi Oktariza; Asridayani Asridayani (Krinok:Jurnal Linguistik Budaya, 2017)
This thesis studies about factor and effect of materialism found in Angel gracia’s FromPrada to Nada Film. Factor and effect of materialsm caused by main character in From Prada toNada film. The main character is Mary. The goals of this thesis are to explain the factor and effectof Materialism. The reseacher uses social perspective. In this thesis, the reseacher uses qualitativemethod, because this method helps the reseacher to present the data in the form of sentence, verbaland phrase. The reseacher describes and analyzes about sentences and dialogues of character inFrom Prada to Nada film. Then, the reseacher uses Sociological Approach to be analyzed. By usingthe qualitative method, the reseacher also makes the reader understand this thesis easily. There aretwo kinds of results in this thesis, they are factor and effect of materialism. The factor ofmaterialism influence Mary’s character in From Prada to Nada Film. There are the death of theirfather and the crisis economic caused by amount debt or bankrupt. In other hand, the reseacher getsthe positive effect. There is being well motivated and solidarity. Then the reseacher gets negativeeffect in this film that consist of disappointment and depression.Key Word: Materialism, From Prada to Nada, Sociological Approach.